Ritual Communication in the Magibung Tradition in Mataram City, West Nusa Tenggara Province: A Study of Hindu Religious Symbols - Suarjaya, I Nyoman Alit; Dikta, Putu Gede Asnawa (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
Indonesia, as a country rich in culture, has thousands of traditions, one of which is the megibung tradition inherited by Hindus in the city of Mataram. This tradition is not merely a communal dining activity, but is also filled with symbols and meanings that reflect the values of togetherness, spirituality, and the relationship between humans and God, fellow humans, and nature. This study aimed to identify the forms of ritual communication contained in the megibung tradition and to understand the meanings of the Hindu symbols within it. The research employed a qualitative method with a phenomenological approach, as this approach allowed the researcher to deeply understand the experiences and meanings perceived by the community. Three theories are used to strengthen the analysis, namely symbolic interactionism, communicative action theory, and phenomenology. These three theories are interrelated and capable of explaining the dynamics of communication, symbols, and collective actions that occur in the megibung tradition. Research data were collected through observation, interviews, and documentation. The results showed that ritual communication in the megibung tradition is reflected through the offering process and the sense of togetherness in the communal meal. The symbols used contain spiritual messages, social ethics, and cultural values, which are important for the Hindu community in Mataram to understand and preserve.